PEMBUATAN MULTIMEDIA INTERAKTIF MENGGUNAKAN MOODLE PADA KOMPETENSI MENGAMATI GEJALA ALAM DAN KETERATURANNYA UNTUK PEMBELAJARAN SISWA SMA KELAS XI SEMESTER I - Husnul Hamdi (Universitas Negeri Padang, 2013)
Abstract—Purpose of this research were to determine the validity of Interactive Multimedia,to describe the Interactive Multimedia, and determine the practicality and effectivity of application Interactive Multimedia in learning process.Type of research is Research and Development (R&D) by using before-after experimental design. Objects of the research are Interactive Multimedia and the students in grade XI IPA 1 SMAN 3 Padang with 31 people. Data collection instruments were used in this research were: validity test sheet, practicality sheet and student learning outcomes test sheet. Products and data analysis technique used the analysis of the validity of the product, analysis of the practicality and analysis of effectivity. Based on the analysis of data can be presented three results of the study. First, Interactive Multimedia produced is valid with value 80,57. Second, Interactive Multimedia by using Moodle have good design with the main menu design, introduction, about, guidance, materials, exercises, quizzes, and chat . Third, the result of interactive multimedia is practice with an average value of practicality by Physics teacher is 90.56% and 82.39% practicality by students. Interactive Multimedia in physics teaching have significantly improve to student learning outcomes. Keywords : interactive multimedia, Moodle, physics learning